CHOICE OF ENTRY MODE INTO THE INTERNATIONALISATION PROCESS BY DOMINANT SPANISH HOTEL CHAINS - García de Soto Camacho, Elena; Álvarez Torrescusa, Manuela (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2018)
<span style="font-family: ’Arial’,sans-serif; font-size: 10pt; mso-fareast-font-family: ’MS Mincho’; mso-ansi-language: EN-GB; mso-fareast-language: AR-SA; mso-bidi-language: AR-SA; mso-bidi-font-weight: bold; mso-bidi-font-style: italic;" lang="EN-GB">This paper focuses on the development of an explicative model regarding the entry mode into a new market as chosen by Spanish hotel chains. Two types of variables have been analysed: some which refer specifically to the destination country, including its potential and cultural distance and others which depend on the company itself, such as its financial situation, the experience gained previously in the country or the company’s degree of internationalisation. Several hypotheses have been put forward and empirically tested using secondary data.